2017
DOI: 10.1001/jamaophthalmol.2017.2697
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Maternal Preeclampsia With Infant Risk of Premature Birth and Retinopathy of Prematurity

Abstract: IMPORTANCE Studies report conflicting associations between preeclampsia and retinopathy of prematurity (ROP). This study provides explanations for the discrepancies to clarify the relationship between preeclampsia and ROP.OBJECTIVE To evaluate the association of maternal preeclampsia and risk of ROP among infants in an unrestricted birth cohort and a restricted subcohort of preterm, very low birth weight (P-VLBW) infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…GA at birth may be an important modifier of relationships between maternal PE and infant morbidity. Studies of VPT infants, representing a truncated GA interval similar to that of our study, have shown associations between maternal PE exposure and reduced rates of brain damage and retinopathy [7,12]. The latter population-based study also included an evaluation over the total span of GA which revealed an increased risk of ROP in relation to PE exposure.…”
Section: Discussionsupporting
confidence: 65%
“…GA at birth may be an important modifier of relationships between maternal PE and infant morbidity. Studies of VPT infants, representing a truncated GA interval similar to that of our study, have shown associations between maternal PE exposure and reduced rates of brain damage and retinopathy [7,12]. The latter population-based study also included an evaluation over the total span of GA which revealed an increased risk of ROP in relation to PE exposure.…”
Section: Discussionsupporting
confidence: 65%
“…First, the confounders varied between different studies; some studies performed fully adjusted analyses, while others performed partially adjusted analyses. Moreover, maternal factors such as preeclampsia [42] and maternal diabetes [43] were seldom included as potential confounders in these studies. Second, moderate heterogeneity was found among the included studies.…”
Section: Plos Onementioning
confidence: 99%
“…These data are further supported by epidemiologic data in other forms of placental insufficiency demonstrating ROP protection [184]. Shulman et al [176], further suggest that prematurity, while necessary for ROP risk, may confound the measured association between maternal preeclampsia and ROP. Certainly the etiologic basis for preterm delivery is varied in most populations, particularly the relatively smaller population delivering in the ROP risk window prior to 32 weeks gestation.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 72%
“…oxygen targets), and infant GA at birth influence the measured affect. This is highlighted in a recent publication by Shulman et al [176], who found that preterm infants with GA and BW risk for ROP (< 32 weeks and 1,500 g) demonstrated ROP protection with preeclampsia; however, infants with no GA or BW risk for ROP, GA at birth ~38 weeks, had an increased co-occurrence of ROP and preeclampsia. Thus, it is important to consider the population demographics when analyzing the relationship between preeclampsia and ROP.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 97%
See 1 more Smart Citation